"Recognition of heart attack symptoms and treatment-seeking behaviors: a multi-center survey in Tehran, Iran" - Elnaz Shahmohamadi; Mojtaba Sedaghat; Arash Rahmani; Farnoosh Larti; Babak Geraiely (BMC, 2023)
Abstract Background In acute myocardial infarction (AMI), timely recognition of symptoms and early hospital presentation positively affect patient morbidity and mortality. Due to the high burden of ischemic heart disease in Iran, this study aimed to identify factors affecting the level of knowledge, responses at the time of AMI onset, and sources of health information among the Iranian population. Method This cross-sectional study was conducted in three tertiary hospitals in Tehran, Iran. An expert-validated questionnaire was used to obtain data. A total of 400 individuals were enrolled. Result Among the respondents, 285 people(71.3%) considered "chest pain or discomfort," and 251 (62.7%) regarded "pain or discomfort in the arm or shoulder" as MI symptoms. Approximately 288 (72.0%) respondents had poor knowledge of the AMI symptoms. Knowledge of symptoms was higher among those with higher levels of education, those with medical-associated jobs, and those who resided in the capital areas. Major risk factors identified by the participants were: anxiety (340)(85.0%), obesity (327)(81.8%), an unhealthy diet (325)(81.3%), and the presence of high LDL levels (258)(64.5%) and Diabetes Mellitus (164)(41.0%) were less appreciated. Calling an ambulance (286)(71.5%) was the most common treatment-seeking behavior in the case of a suspected heart attack. Conclusion It is vital to educate the general population about AMI symptoms, particularly those with comorbidities at the greatest risk for an AMI episode.